Pore-water pressure characteristics of two instrumented residual soil slopes - Rahardjo, Harianto (2011)
Responses of pore-water pressures in unsaturated soil slopes during rainfall have major influences in triggering slope failures. Two fully instrumented residual soil slopes located in two major geological formations in Singapore, that are Bukit Timah Granite and sedimentary Jurong Formation, were monitored for a period of several months. Real-time monitoring systems in the slopes were used to provide pore-water pressure, rainfall, and ground water level data. Characteristics of pore-water pressure distributions in both slopes during rainfalls were studied and compared. The monitoring results indicate that the Bukit Timah Granite residual soil slope has a deeper ground water table and a thicker unsaturated zone than the sedimentary Jurong Formation residual soil slope. A higher permeability of the Bukit Timah Granite residual soil results in a faster change in negative pore-water pressure due to rainwater infiltration as compared to those of the sedimentary Jurong Formation residual soil. Consequently, changes in shear strength and factor of safety of the Bukit Timah Granite residual soil slope during rainfall have different characteristics than those of the Jurong Formation residual soil. The differing characteristics of pore-water pressure responses during rainfall in these two residual soils are analyzed and highlighted in the paper.